PENGARUH INOVASI LAYANAN DAN STANDAR OPERASIONAL PROSEDUR TERHADAP KUALITAS LAYANAN DI PUSKESMAS KECAMATAN PULOGADUNG JAKARTA TIMUR - Octavianus Marojahan; Arief Rachmawan Assegaf (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2025)
This study was conducted to determine the effect of service innovation and standard operating procedures on service quality at the Pulogadung District Health Center, East Jakarta. This study uses a quantitative approach. The population in this study was 50 employees. The sampling technique in this study used the census sampling type. The data analysis method used in this study is multiple and simple linear regression. The research results show that: 1) Together, service innovation and standard operating procedures have a positive influence on service quality; 2) Service innovation has a positive effect on service quality; dan 3) Standard operating procedures have a positive effect on service quality at the Pulogadung District Health Center, East Jakarta.